Incentives for smoking cessation in pregnancy. (30th September 2020) - Tappin, D; Bauld, L
Abstract: Issue/problem: Most pregnant smokers reply 'Yes' when asked 'Do you want to stop smoking?'. This is usually an honest answer but often without intention. About 10% who intend to quit are likely to attend smoking cessation services. Even with good quality counselling and the offer of nicotine replacement therapy only about 3-5% quit. How can the other 90% be reached? There are two approaches: Redirect counselling away from specialist cessation practitioners and build capacity among all health care workers. This is attractive spreading counselling to health care workers who meet pregnant smokers during routine consultations requiring little resource after training for example General Practitioners, Midwives and Obstetricians. However limited time for training and subsequent counselling endangers the quality and quantity of counselling delivered. Increase the proportion of women who intend to quit smoking during pregnancy by providing a financial incentive payment for engaging with specialist cessation practitioners and quitting. This policy allows counselling to be delivered by specialists and potentially draws in a larger proportion of pregnant smokers, as many as 50%. Results: Financial incentives have increased the proportion of smokers who quit by late pregnancy in two large randomised controlled trials. The proportion increased by more than 100%. Local service pilots of financial incentives have seen marked increases in smokers who attend and quit. Lessons: There are a number of ways to increase smoking cessation among pregnant women. Research evidence should be translated into effective service models to decide which strategy is most cost-effective. Key messages: Counselling is important; however, it has to be sufficient and of good quality. Drawing more pregnant smokers into cessation services will increase the proportion who intend and manage to quit. This may work better than expecting all health care workers to give effective counselling.